Via di accesso innovativa alla lamina quadrilatera: Anterior Combined Endopelvic (ACE) approach - Rocca, G.; Bolcic, S.; Patronis, D.; Boero, E. (Lo Scalpello - Journal, 2018)
ACE APPROACH: INNOVATIVE APPROACH TO THE QUADRILATERAL LAMINA We have designed and performed a new anterior pelvic approach for eight years. This has enabled us to obtain a wide direct visibility, and to improve our clinical and functional outcomes. Being easy to perform, it allows for reduction of surgical times. The learning curve is quicker, therefore it is intended to be an opportunity for those young surgeons who want to undertake this rather complex surgery.